Pengaruh internal locus of control terhadap intensi kewirausahaan pada orang Jawa - Moh. Sarifudin S. Auna (Psychological Journal: Science and Practice, 2021)
Cultural inﬂuence on entrepreneurship has been an ongoing scientiﬁc interest for more than three decades. Indonesia as a multi-cultural country needs to internalize local values in entrepreneurship. One of the internal factors of individuals associated with local values is the internal locus of control in inﬂuencing the entrepreneurial intentions possessed by the Javanese. This research examines the inﬂuence of culture in entrepreneurship that has not been explored much by psychology research in the ﬁeld of entrepreneurship. The purpose of this study tested the internal inﬂuence of locus of control on entrepreneurial intentions on Javanese. The research method uses a quantitative approach with ex-post facto design, the sample in the study as many as 66 respondents with incidental sampling techniques, instruments used internal locus of control and entrepreneurial intentions, data analysis used is linear regression analysis with a signiﬁcance level of 0.05. The results of the hypothesis test showed the internal locus of control signiﬁcantly affected the entrepreneurial intention with a value of p 0.117.